2013
DOI: 10.1103/physrevlett.111.138101
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Motility of a Microswimmer in Rigid and Elastic Confinement

Abstract: We analyze the effect of confining rigid and elastic boundaries on the motility of a model dipolar microswimmer. Flexible boundaries are deformed by the velocity field of the swimmer in such a way that the motility of both extensile and contractile swimmers is enhanced. The magnitude of the increase in swimming velocity is controlled by the ratio of the swimmer-advection and elastic time scales, and the dipole moment of the swimmer. We explain our results by considering swimming between inclined rigid boundari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 33 publications
(41 reference statements)
2
51
1
Order By: Relevance
“…We will first provide a brief summary of wall effects reported so far in the literature before discussing our results. The fact that the wall enhances motility is reported in several papers [12,[43][44][45][46][47][48]. However, we must stress, as we found, that this is not always true.…”
Section: On the Non Monotonous Behavior Of The Swimmer Velocity Ascontrasting
confidence: 52%
See 1 more Smart Citation
“…We will first provide a brief summary of wall effects reported so far in the literature before discussing our results. The fact that the wall enhances motility is reported in several papers [12,[43][44][45][46][47][48]. However, we must stress, as we found, that this is not always true.…”
Section: On the Non Monotonous Behavior Of The Swimmer Velocity Ascontrasting
confidence: 52%
“…Bilbao et al [45] analyzed a model inspired by nematode locomotion by simulation and found that walls enhance the speed. Ledesma et al [46] treated a dipolar swimmer bounded both by rigid or an elastic tube and obtained a speed enhancement due to walls.…”
Section: On the Non Monotonous Behavior Of The Swimmer Velocity Asmentioning
confidence: 99%
“…Second, the collective behaviour of microswimmers has been studied at moving boundaries [46,53,54] but all of which were of fixed shape. Bacteria and active particles near flexible boundaries have not yet been explored systematically and it is interesting to understand how clustering and trapping phenomena are modified for flexible boundaries [55]. Our case of a flexible polymer chain is therefore one of the simplest key examples to proceed along this important direction.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] An important consideration in mechanical microswimming is the way elastic forces interact with the fluid and any external forces present in determining the motion. In the literature different aspects of these forces that have been studied are the elasticity of the swimming mechanism (such as those involving flagella and cilia), [14,38] the influence of flexible surrounding walls if the motion occurs close to them, [39,40] and even the elasticity (or the viscoelasticity) of the ambient fluid. [8,[41][42][43][44][45][46][47][48][49] In addition, the advantage of having elastic bodies has been investigated for the forced motion of microbodies, such as capsules driven through constrictions.…”
Section: Introductionmentioning
confidence: 99%